2018
DOI: 10.4103/ejd.ejd_271_17
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of periodontal compromise in teeth indicated for undergoing endodontic treatment: A clinical study

Abstract: Objective:The aim of this study was to evaluate the periodontal status of teeth indicated for undergoing endodontic treatment.Materials and Methods:Two hundred and nine teeth were evaluated using probing depth tests at three vestibular and three palatine/lingual sites before the patients underwent treatment. Teeth that presented up to 3-mm probing depth were considered as healthy. Those that presented at least one site with probing depth >3 mm were considered periodontally compromised. The data were statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…31 A study evaluating periodontal status of teeth indicated for undergoing endodontic treatment reported the rate of the periodontally compromised teeth to be almost 20%. 32 The present results demonstrated marginal bone loss of more than one-third of the root length in almost 29% of teeth. Though previous studies reported an association between marginal bone level and AP, 13,33 our results did not demonstrate any significant variations in periapical condition regarding the marginal bone loss.…”
Section: Discussionsupporting
confidence: 57%
“…31 A study evaluating periodontal status of teeth indicated for undergoing endodontic treatment reported the rate of the periodontally compromised teeth to be almost 20%. 32 The present results demonstrated marginal bone loss of more than one-third of the root length in almost 29% of teeth. Though previous studies reported an association between marginal bone level and AP, 13,33 our results did not demonstrate any significant variations in periapical condition regarding the marginal bone loss.…”
Section: Discussionsupporting
confidence: 57%